THE METHOD AND ALGORITHMS FOR IDENTIFICATION OF DYNAMIC OBJECTS ON BASIS OF INTEGRAL EQUATIONS - Diachuk, Aleksandr Anatolievich; Kostyan, Nataliya Leonidovna; Sytnik, Aleksandr Alekseevich; Halmuhametova, Feruza Arslanbekovna (Kamianets-Podilskyi National Ivan Ohiienko University, 2013)
In work questions of development of numerical algorithms of identification for operated dynamic objects on the basis of integrated models are considered.